Learning Persistence in Online Learning Assisted by English Module Media - Azizatul Banat; Mariska Febrianti (Scope : Journal of English Language Teaching, 2023)
This research aims to determine the learning persistence in online learning assisted by English module media for English general course (MKU) students after the spread of the Corona virus and entering an endemic period. The population in this research was 1st semester students of Physical Education Study Program, Faculty of Teacher Training and Education, the University of Dehasen Bengkulu,  in Academic Year of 2022/2023. Sampling used was random sampling with a sample of 90 people who were students of class A1, A2, A3. Data collection techniques employed triangulation using questionnaires, interviews and observations. The research method was a descriptive research with research data using qualitative data. The data analysis technique used using a Likert scale to obtain questionnaire data to determine student’s learning persistence based on indicators on the instruments that have been compiled, and then the data obtained will be changed into percentage data. The results show that the average level of learning persistence for students in online learning assisted by English module media for English general course (MKU) students after the spread of the Corona virus and entering an endemic period based on the fractional indicator was not delaying work completion time (81.9), always take advantage of opportunities (80 always trying to succeed in carrying out tasks (81.1), never satisfied with the results obtained (76), always want to try more challenging jobs (76), always dream and wake up from dreams (80), Work according to top priority (80), Able to solve problems (75,8), Connect with friends who are active (73,8), therefore the average indicator learning persistence and problem solving ability for students is 78.2. From these results it can be interpreted based on the scale range of criteria for interpretation of the score of the respondent's achievement level, thus the interpretation of learning persistence for students in online learning with the help of English module media in general English courses is strong.